Activated carbon fiber/Fe3O4 composite with enhanced electromagnetic wave absorption properties. Issue 61 (15th October 2018) - Sun, Qilong; Sun, Lei; Cai, YingYing; Ji, Tao; Zhang, Guangyu
Abstract : To obtain a low-density material that is capable of absorbing electromagnetic waves over a wide bandwidth, an activated carbon fiber/Fe3 O4 composite material (ACF/Fe3 O4 ) was prepared using an in situ reduction method. Abstract : To obtain a low-density material that is capable of absorbing electromagnetic waves over a wide bandwidth, an activated carbon fiber/Fe3 O4 composite material (ACF/Fe3 O4 ) was prepared using an in situ reduction method. Scanning electron microscopy images show that Fe3 O4 nanoparticles, approximately 10–40 nm in size, were spread uniformly over the surface of the ACF. The resulting composite exhibited superparamagnetic behavior at room temperature. The ability of the ACF and ACF/Fe3 O4 composite to absorb electromagnetic waves over a frequency range of 8.2–18 GHz was measured using the arch method. The results showed that the maximum reflectivity of an ACF felt was −12.9 dB at 18 GHz, and the effective microwave-absorbing bandwidth ( R < −10 dB) was 1.9 GHz (16.10–18 GHz). The absorption performance of the ACF was greatly enhanced by being loaded with Fe3 O4 nanoparticles; the maximum reflectivity of the 2 mm layer of the ACF/Fe3 O4 composite was −30.07 dB at 16.45 GHz, and the effective bandwidth ( R < −10 dB) increased to 8.62 GHz (9.38–18 GHz). Coating with nano-Fe3 O4 magnetic particles can effectively improve the absorption of electromagnetic waves by the ACF, and this technique therefore has great potential for application to the field of electromagnetic shielding.